2023
DOI: 10.1080/21645515.2023.2222648
|View full text |Cite
|
Sign up to set email alerts
|

Concerns related to the interactions between COVID-19 vaccination and cancer/cancer treatment were barriers to complete primary vaccination series among Chinese cancer patients: A multicentre cross-sectional survey

Abstract: COVID-19 vaccination is effective for cancer patients without safety concerns. However, COVID-19 vaccination hesitancy is common among cancer patients. This study investigated factors affecting primary COVID-19 vaccination series completion rate among cancer patients in China. A multicentre cross-sectional study was conducted in four Chinese cities in different geographic regions between May and June 2022. A total of 893 cancer inpatients provided written informed consent and completed the study. Logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Our study further demonstrated that negative attitudes towards vaccines and perceived barriers were both associated with reduced acceptance of the second COVID-19 booster Dose. Similar results were found in immunocompromised cancer patients, which strengthened the necessity of vaccination among specific populations ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our study further demonstrated that negative attitudes towards vaccines and perceived barriers were both associated with reduced acceptance of the second COVID-19 booster Dose. Similar results were found in immunocompromised cancer patients, which strengthened the necessity of vaccination among specific populations ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 80%
“…Our study further demonstrated that negative attitudes towards vaccines and perceived barriers were both associated with reduced acceptance of the second COVID-19 booster Dose. Similar results were found in immunocompromised cancer patients, which strengthened the necessity of vaccination among specific populations (34,35). Our study is the first to investigate the relationship between the willingness of PLWH in China to receive the second COVID-19 booster dose and the six main dimensions of the HBM.…”
Section: Discussionsupporting
confidence: 77%
“…Knowing that they are a priority for vaccination will increase their con dence to seek health care services. Additionally, vaccination campaigns and emphasis on uptake for vulnerable populations, such as cancer patients, can encourage them to prioritize routine medical visits, including cancer-related appointments (47). Initiating a Covid-19 vaccination program may imply a commitment to greater health care and patient safety and instill con dence in the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was 41.8% in Bosnia and Herzegovina (29), 50.5% in Tunisia (30), 66.0% in Mexico (31), and 19.5% in Korea (32). Despite the official recommendations, the prevalence only ranged from 12.6 to 58.8% among cancer patients in China (33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%